The Columbia history of Western philosophy - Popkin, Richard H. (Richard Henry), 1923-2005 (Columbia University Press, 1999)
Richard Popkin has assembled 63 leading scholars to forge a chronological account of the development of Western philosophical traditions. From Plato to Wittgenstein and from Aquinas to Heidegger, this volume provides lively, in-depth, and up-to-date historical analyses of all the key figures, schools, and movements of Western philosophy. Each chapter includes an introductory essay, and Popkin provides notes that draw connections among the separate articles. The rich bibliographic information and the indexes of names and terms make the volume a invaluable resource.
Simultaneously published: The Pimlico history of Western philosophy. London : Pimlico, 1999.
Keywords: Philosophy -- History.; Philosophie -- Histoire.; PHILOSOPHY -- History & Surveys -- Modern.; PHILOSOPHY -- History & Surveys -- General.; PHILOSOPHY -- General.; Philosophy; History